Development of a body condition score for the mountain chicken frog (Leptodactylus fallax). Issue 3 (14th April 2018) - Jayson, Stephanie; Harding, Luke; Michaels, Christopher J.; Tapley, Benjamin; Hedley, Joanna; Goetz, Matthias; Barbon, Alberto; Garcia, Gerardo; Lopez, Javier; Flach, Edmund
Abstract : The Critically Endangered mountain chicken frog ( Leptodactylus fallax ) has undergone drastic population decline due to habitat loss, hunting, invasive species, and chytridiomycosis. In response, several partner institutions initiated a conservation breeding program. It is important to maintain the captive population in good health. Therefore the program partners have recommended establishment of protocols for health examination of the species, including body condition assessment. Visual body condition scoring is a useful means to assess body condition in zoo animals for which regular bodyweight measurements are impractical or associated with capture‐related stress. In this study, the authors developed a visual body condition score for the mountain chicken frog based on an ordinal categorical scale from 1 to 5 (1 = lowest body condition, 5 = highest body condition) using anatomical features that vary with total body energy reserves. Veterinary staff, animal managers, keepers, researchers, and students subsequently used the body condition score to assign scores to 98 mountain chicken frogs (41 male, 57 female) aged between 8 months and 12 years housed in five zoos in the UK and Jersey between February and March 2016. Body condition scores showed moderate (rho = 0.54; males) to strong (rho = 0.6; females) correlation with the scaled mass index, an objective measure of total energy reserves. The majority of pairwise comparisons between scores showed slight to substantial intra‐observer agreement (93.8%) and slight to almost perfect inter‐observer agreement (97.2%). Cases of poor agreement were likely due to limited observer experience working with the species.